Evaluation of Solar-Energy Dryer Systems on Drying Behaviour and Quality Attributes of Amaranth Grains - Ronoh, Erick K.; Kanali, Chr istopher L.; Mailutha, Joseph T.; Shitanda, Douglas (Science and Engineering Publishing Company, 2012)
This work aimed at evaluating the thin layer drying behaviour of amaranth grains (Amaranthus cruentus) and comparing the quality of the grains dried under solar-energy tent dryer systems and the open sun. The dryers were covered with clear, yellow and nectarine diffused polyvinyl chloride (PVC) materials of 200 micron thickness whose transmissivities were 90%, 85% and 82%, respectively. The ambient temperature and relative humidity ranged from 23.3～33.5oC and from 24% ～ 46%, respectively, while the inside temperature and relative humidity in the solar dryers ranged from 30.4～50.7oC and from 15%～44%, respectively. Fresh amaranth grains with an initial moisture content ranging from 66.7% ～ 68.8% dry basis (d.b) were dried under both conditions for 8 hours to an equilibrium moisture content of about 7% d.b. The quality attributes assessed were colour, hardness and crude protein content. The findings showed no significant effect of colour of cover material on the grain quality. The study demonstrates that natural convection solar tent dryers covered with PVC materials enhance the thin layer drying rate of amaranth grains without significantly affecting their quality.
Keywords: Thin Layer; Amaranth Grains; Solar-energy Tent Dryers; Open Sun; Quality